Desenvolvimento de inovações tecnológicas na pequena empresa brasileira pelo uso intuitivo de metodologias de gestão estratégica: o caso Sat Paraná - Salamacha, Luciano Miguel (2005)
The present work aims to verify if the development of technological innovations in a small Brazilian company can occur by the intuitive use, by its main administrator, of concepts of strategic administration and of technological strategies. Therefore, it presents bibliographical revision on the relative theoretical concepts referring to the business strategy, emerging strategies, competitive strategies, strategic methodologies - specifically the matrix SWOT and the Porter’s Five Competitive Forces - planning strategic, technological innovation, ways of access to the technology, technological strategies and technological innovation in the small Brazilian company. It is used of a study of case of the company Ensacadeiras Sat Paraná Ltda that, besides framing as a small company according to elect criteria for this work, it has been promoting a series of technological innovations since its ten years of existence, inclusively with the industrial property registration, without the structured use of administration methodologies. Therefore, three sessions of interviews were accomplished with the founder and main manager of the company by the use of a previous itinerary segmented in: subjects for setting the company in a context and its main manager; subjects concerning to the company; and subjects concerning to the theoretical referential. It follows that the development of technological innovations in Sat Paraná occurs because its owner main managener acts by the intuitive and partial use of the concepts presented in the theoretical referential of this work, notedly in two fundamental aspects: a) the acquired knowledge of the owner along his professional career (to know how to do) added to the access and know-how of the ways to accomplish the conceived technology (ways) that compensate the lack of an acquired academic knowledge (to know); b) the practice of the owner to offer the knowledge about operation of fertilizer factories as a way for the commercialization of Sat Paraná's equipments demonstrates that the process of technological innovation of the company often keeps stimulated by the opportunity of identifying needs, as much declared as latent, of its customers.